2017
DOI: 10.1136/heartjnl-2017-311560
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and clinical predictors of valve dysfunction and aortic dilation in bicuspid aortic valve disease

Abstract: ObjectiveBicuspid aortic valve (BAV) is associated with early valvular dysfunction and proximal aorta dilation with high heterogeneity. This study aimed to assess the determinants of these complications.MethodsEight hundred and fifty-two consecutive adults diagnosed of BAV referred from cardiac outpatient clinics to eight echocardiographic laboratories of tertiary hospitals were prospectively recruited. Exclusion criteria were aortic coarctation, other congenital disorders or intervention. BAV morphotype, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 30 publications
5
55
0
6
Order By: Relevance
“…Additionally, the authors observed no differences in ascending aorta diameter between the BAV phenotypes,1 which is also consistent with our results 2. In our meta-analysis, we demonstrated that the aortic root diameter in BAV type I was significantly larger (on average of 1.66 mm/m 2 indexed and 2.0 mm non-indexed diameter of aorta at the level of sinus of Valsalva) in comparison to BAV type II.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the authors observed no differences in ascending aorta diameter between the BAV phenotypes,1 which is also consistent with our results 2. In our meta-analysis, we demonstrated that the aortic root diameter in BAV type I was significantly larger (on average of 1.66 mm/m 2 indexed and 2.0 mm non-indexed diameter of aorta at the level of sinus of Valsalva) in comparison to BAV type II.…”
supporting
confidence: 92%
“…Several previous studies reported significant disparities in the relationship between aorta dilation and BAV characteristics. However, the excellent study of Evangelista et al allows us to feel closer to solving the mystery of BAV morphology and its impact on aortic diameter 1. Their multicentre study on the impressive and the largest ever population of 852 patients with BAV, using prespecified protocol and core lab review of all images to define BAV morphology and function along with aortic dilation, covered multiple aspects (valve dysfunction and proximal aorta dilation) of heterogeneous BAV population.…”
mentioning
confidence: 99%
“…Exclusion criteria were a non-definitive diagnosis of BAV or the presence of another connective tissue disorder. From 852 patients included in our previous study,18 256 agreed to undergo family screening. Anamnesis, three-generation pedigree, physical examination and transthoracic echocardiography were performed in each index case.…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of Heart , Evangelista and colleagues1 sought to identify phenotypic predictors of valve dysfunction and aortic root dilation in a series of 802 consecutive adults diagnosed with BAV at eight tertiary care hospitals. As in previous studies, BAV leaflet morphology characterised by fusion of the right and left (RL) coronary cusps was most common (73%), followed by fusion of the right and non-coronary cusps (24%).…”
mentioning
confidence: 99%